Is the globalization influencing the primary energy consumption? The case of Latin America and Caribbean countries - Koengkan, Matheus (Cadernos UniFOA, 2017)
This article investigates the relationship between globalization and primary energy consumption in twelve Latin America and Caribbean countries from 1991 to 2012 using the auto-regressive distributive lag (ARDL) methodology. The elasticities results showed that increase of 1% on index globalization exerts a positive impact of 0.4449 % above the primary energy consumption. The variables gross domestic product (GDP) and dioxide carbon emissions (CO2) exert a positive impact in short and long-run, as well as the variable capital account openness has a negative effect in long-run.